DESENSITISASI SISTEMATIK DENGAN DZIKIR TASBIH UNTUK MENURUNKAN SIMTOM KECEMASAN PADA GANGGUAN FOBIA SPESIFIK - Azmarina, Rani (HUMANITAS, 2015)
AbstractThis research aim is to know the effect of systematic desensitization by tasbeeh dhikr to reduce anxiety symptoms of specific phobia. It was a quasi experimental study with pretestposttest control group design. The data collection was using phobia anxiety scale which refers to four aspects which were physiological, emotional, cognitive and behavioral, then conducted interviews and observations. Intervention was carried out four times during the two weeks meeting. This research subjects were female students who had a phobia from certain object consisting of six people, three people as the experimental group and the other three people were the control group. The results of the analysis, which was conducted using Mann Whitney test showed significant results with the value of p= 0.046 (p < 0,05). The result from Friedman test also showed significant results with p= 0.028 (p < 0,05). Mann Whitney analysis results showed that the interventions have a significant influence on the emotional and behavioral aspect with p = 0.046, whereas onphysiological and cognitive aspects, the intervention did not have significant influence with the p value each of which p = 0.261 (p > 0.05) for the physiological and p = 0.376 (p> 0.05) for cognitive. The conclusion is that systematic desensitization by tasbeeh dhikr may reduce the anxiety symptom of specific phobia. Keyword: specific phobia, systematic desensitization by tasbeeh dhikr, the symptoms ofanxiety